Perbedaan Pengetahuan dan Sikap Sebelum dan Sesudah Penyuluhan Gizi Seimbang secara Daring di SDN Tanjungrejo 4 Kota Malang - Saputri, Dian Eka; Aroni, Hasan; Supariasa, I Dewa Nyoman (NUTRITURE JOURNAL, 2023)
Background: Based on the results of Basic Health Research (2018), it is known that the prevalence of nutritional status of children aged 5-12 years based on Body Mass Index by age is 2.4% very thin, 6.8% thin, 10.8% fat and 9.2% obese. The problem of malnutrition in children is due to the lack of consuming foods that contain energy, high-quality protein, and minerals. In contrast, nutritional problems are caused by excessive consumption of energy, fat, sugar, and salt, but tend to consume fewer vegetables and fruits. Excessive intake of these nutrients is also accompanied by low physical activity. The purpose of this study was to determine the differences in knowledge and attitudes of school-age children before and after counseling on balanced nutrition for school-age children. Methods: The type of research used is pre-experimental research with a One Group Pretest Posttest design. This research was conducted in October 2021 at SDN Tanjungrejo 4 Malang City. The sampling technique used was purposive sampling with a total sample of 27 school-age children. Research Results: The mean value of respondents’ knowledge before counseling was 67.59. After receiving counseling the average value of knowledge increased to 74.26. The average value of the attitude of the respondents before the counseling was 51.15. After receiving counseling the average attitude value of the respondents increased to 54.22. This shows that there is a significant difference in knowledge (p-value = 0.001 (Sig <0.05)) and attitude (p-value = 0.000 (Sig <0.05)) between before and after the balanced nutrition counseling. Conclusion: There are differences in knowledge and attitudes of students in grades III and IV at SDN Tanjungrejo before and after counseling on balanced nutrition.